282 The relationship between exercise frequency and development of knee osteoarthritis (OA) in young & middle-aged population using national health insurance sharing Service (NHISS). (3rd March 2020) - Lee, Soyoung; Lee, Sae Yong
Abstract : Background: There has been controversy about whether exercise has positive or negative influence in development of OA. However, there are lack of epidemiological studies investigating risk of exercise with large population and long-term follow up period. Objective: The aim of the study is to identify the relationship between the exercise frequency and development of OA in different population groups by gender (male, female), age (20s, 30s, 40s), and BMI (normal, overweight, obesity). Design: Cohort study Setting: This 186, 779 population medical database from 2003 to 2016 was offered by NHISS originally on the purpose of research regarding cruciate ligament (CL) population. Patients (or Participants): This population consists of randomly selected 169, 183 (male=88, 696, female=80, 487; age=31.19±7.75 yrs) Korean people without having any acute lower limb injuries and 17, 596 of CL injured population (male=11, 881, female=5, 715; age=31.34±7.53 yrs) patients between 2003 to 2005. Interventions (or assessment of risk factors): Exercise frequency was divided into five categories: Never, 1–2 times, 3–4 times, 5–6 times, Everyday per week. Analysis was conducted within each different groups by gender, age, and BMI. Main outcome measurements: Cox proportional-hazard model was used to determine a risk of exercise for knee OA until 2016. Adjusted hazard ratios (HR) and 95% confidential intervals (CIs) were estimated. Results: In age 30s, people who exercise 3–4 times (HR: 1.28; 95%CI: 1.02–1.61) were having slightly higher risk for OA development than healthy population. Obese people exercising 3–4 times (HR: 1.80; 95%CI: 1.12–2.90) and 5–6 times (HR: 2.66; 95%CI: 1.14–6.20) also showed higher risk for incidence of OA than the normal. Exercise frequency and OA incidence did not show any significant relationship in female, male, 20s, 40s, and overweight groups. Conclusions: Exercise might not be a critical risk factor for onset of OA except for the obese population. This result provides potential suggestion for exercies to be used as a treatment strategy or preventative measure for OA patients.